Answer:
Therefore the length of QP = 3.4 units
Step-by-step explanation:
Given:
PQ = 2x + 1
XF = 7x - 4
PF = x
Q is the mid poimt of XF
∴ XQ = QF
QF = PQ - PF ..........( Q - F - P )
= 2x + 1 - x
∴ QF = x + 1
∴ XQ = QF = x + 1
TO Find:
QP = ?
Solution:
By Addition Property we have
[tex]XP = XQ + QF+PF ..........(X-Q-F-P)\\\\[/tex]
[tex]XF + PF =XQ + QF+PF ..........(X-Q-F-P)\\[/tex]
Substituting the given values in above equation we get
(7x - 4) + x = (x +1) + (x +1) + x
8x -4 = 3x +2
8x - 3x + 4 + 2
5x = 6
∴ [tex]x = \frac{6}{5}[/tex]
Now we require
QP = (2x + 1)
∴ [tex]QP = 2\times \frac{6}{5} +1\\\\QP = \frac{12+5}{5} \\\\QP =\frac{17}{5} \\\\\therefore QP = 3.4\ unit[/tex]
Therefore the length of QP = 3.4 units